Exploring the Critical Thinking Skills of Analysis and Evaluation in 9th Graders Through the Use of Authentic Materials and the Socratic Method - Iván Aguirre Sánchez (Asociación Colombiana de Profesores de Ingles, 2016)
This research aimed at exploring the interactive role of critical thinking skills and authentic materials in a group of male ninth graders at a private school in Bogotá. These students were observed in order to determine how their written production and oral interaction was shaped when being in contact with a set of teaching units designed from authentic materials such as newspapers and TV broadcasts. These materials were designed after considering the results of a survey in which the participants were asked which topics they would like to work on during the application of this project. The outcomes of the study show that participatns analysed and judged topics using internal evidence and external criteria. These two features of thinking match the stages of human knowledge development initially proposed by Bloom (1974), and lightly modified by Facione (1998). The study also reveals that the quality and quantity of teacher feedback highly affects the quality of learner's production. Teachers' permanent reflection and refinement of techniques such as the Socratic questioning are key factors for obtaining more elaborate responses from EFL learners.